Problems of Desecularizing Nigeria's Political Order - Opeloye, M. O. (2014)
Since the demise of the second republic and the second military intervention in Nigerian politics, Nigeria has been in search of a stable political system. A political bureau was established by the federal government for the purpose of conducting a national debate with a view to enabling Nigerians to make meaningful contributions for the formation of a political system of their choice. Since then, varied opinions have been expressed, some have advocated a one-party system, others a two-party system, while yet others opt for a zero party system.